Green Synthesis and Antibacterial Activity of Silver Nanoparticles Using Ethanolic Extract from Clerodendrum fragrans Leaves - Murniaty Simorangkir; Indah Sitanggang; Floren Miani Sihotang; David Septian Sibarani (Universitas Negeri Medan, 2026)
Green synthesized silver nanoparticles using plant extract (AgNPs) have emerged as promising biomaterials for biomedical applications, particularly as antimicrobial agents. This study aimed to synthesize AgNPs using ethanolic leaf extract of sarang banua (Clerodendrum fragrans) and to evaluate their physicochemical characteristics and antibacterial activity for skin-related applications. C. fragrans leaf contains secondary metabolite bioactive compounds that can be involved in nanoparticle synthesis. In this approach plant-derived phytochemicals functioned as reducing and stabilizing agents. Antibacterial activity was tested using the disc diffusion method followed by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The results of the study showed an average diameter of 114 nm with a polydispersity index (PDI) of 0.5, indicating moderate uniformity.The AgNPs showed strong inhibitory activity against Staphylococcus aureus as a representative skin-associated pathogenic bacteria with an inhibition zone of 11.06 mm. The minimum inhibitory concentration value was 3.375 µg/mL, while the minimum bactericidal concentration value exceeded 27 µg/mL, indicating bactericidal effects at higher concentrations. These findings highlight the potential of C. fragrans-mediated AgNPs as biomaterials for skin-related biomedical applications.